2006
DOI: 10.1002/mrd.20495
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase‐3 regulation of chromatin segregation and cytokinesis in mouse preimplantation embryos

Abstract: Glycogen synthase kinase-3 (GSK-3) is a highly conserved serine/threonine protein kinase implicated in diverse cellular processes. Activity of GSK-3 is essential for meiotic chromatin segregation in oocytes, yet expression and/or function of GSK-3 have not been reported in mammalian preimplantation embryos. Objectives of this study were to characterize GSK-3 protein expression/phosphorylation in mouse preimplantation embryos, to assess the effect of GSK-3 activity inhibition on early mitotic events, and to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…Ser 9 -phosphorylated inactive GSK3B was detected in mice MII oocytes (Acevedo et al 2007b), and we found that this form was more abundant in mature bovine oocytes compared with immature ones. Similarly, in Xenopus, GSK3B was active in GV oocytes and inactivated during maturation in response to progesterone (Fisher et al 1999).…”
Section: Gsk3b Expression In Bovine Oocytes and Surrounding Folliculamentioning
confidence: 67%
See 4 more Smart Citations
“…Ser 9 -phosphorylated inactive GSK3B was detected in mice MII oocytes (Acevedo et al 2007b), and we found that this form was more abundant in mature bovine oocytes compared with immature ones. Similarly, in Xenopus, GSK3B was active in GV oocytes and inactivated during maturation in response to progesterone (Fisher et al 1999).…”
Section: Gsk3b Expression In Bovine Oocytes and Surrounding Folliculamentioning
confidence: 67%
“…Bars: 50 mm. (Acevedo et al 2007b), was used in these studies. The addition of 20 mM of LiCl 2 to bovine COC during IVM led to reduced expansion of cumulus after 24 h of IVM as compared with control ( Fig.…”
Section: Effect Of Gsk3 Inhibitors On Bovine Oocyte Nuclear Maturatiomentioning
confidence: 99%
See 3 more Smart Citations